Mitogenomes provide insight into complex evolutionary history of freshwater and coastal Irrawaddy dolphin (Orcaella brevirostris Gray, 1866) in Thailand and Indonesia - Budi, Trifan; Piyapattanakorn, Sanit; Kreb, Danielle; Yuda, Pramana; Ninwat, Santi; Hardwises, Pornthipa; Prachamkhai, Pimchanok; Senanan, Wansuk; Thongsukdee, Surasak; Phavaphutanon, Janjira; Klinsawat, Worata (Agriculture and Natural Resources, 2022)
Importance of the work: Irrawaddy dolphins have experienced demographic decline. The lack of genetic information might hamper management decisions necessary for restoring population viability. Objectives: To apply population genetics and mitogenome phylogenetic analyses to assess genetic diversity and connectivity among Irrawaddy dolphin populations in Indonesia and Thailand. Materials & Methods: Samples from stranded dolphins were collected from Mahakam River and East Kalimantan, Indonesia and from Songkhla Lake and the Lower and Upper Gulf of Thailand. Based on Bayesian time-scaled phylogeny and pairwise population differentiation, the divergence times were estimated between Irrawaddy dolphin lineages and potential historical factors influencing the observed genetic structure were inferred. Results: The Indonesian populations had lower mtDNA diversity compared to Thailand populations. Pairwise population differentiation and analysis of molecular variance based on the control region supported high differentiation among fragmented Thailand and Indonesian populations (FST = 0.6622, p < 0.0001) with 66.21% variation among groups, except for the Songkhla Lake and coastal Lower Gulf populations. Phylogenetic analyses revealed close relationships between some of the Thai and Indonesian haplotypes, suggesting historical freshwater connectivity. There was a lack of monophyly despite the strong support for the Mahakam River clade in Indonesia. The Mahakam River population started to diversify during the late Pleistocene ( 304.4 Ka; 95% highest posterior density (HPD) = 157.8–505.3 Ka), possibly due to sea-level fluctuation and changes in palaeodrainage systems. Main finding: The results of the genetic diversity and complex evolutionary history of the Irrawaddy dolphin raise conservation concerns and support management strategies aiming to restore population connectivity and reduce the impacts of genetic and demographic stochasticity.